Realisasi Penyusunan Soal Berbasis Hots (Higher Order Thinking Skils) di SMP Negeri 3 Kota Jambi - Netty Hasanah; Amirul Mukminin; Nazurty Nazurty; Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to analyze the preparation of HOTS-based questions in state junior high school 3 Jambi City and its supporting and inhibiting factors. This study uses data collection methods with observation, interviews and documents. This study uses a qualitative analysis technique method that focuses on describing an event and events that have occurred at the time the research was conducted. The results of this study indicate that the preparation of HOTS learning is carried out starting when designing learning activities in lesson plans, during the implementation of learning in class through preliminary activities, core activities, and closing, and also implemented through assignments and Daily Assessments (DA), Mid Semester Assessments (MSA). and Final Semester Assessment (FSA). Supporting factors from the central government through LPMP, City Government/ Jambi City Education Office, MGMP Rayon and MGMP Kota, Education Unit/ Principal. The inhibiting factors for teachers at state junior high school 3 Jambi City are difficulties in determining the stimulus, students are not used to it, lack of references.